(untitled) (Journal of the Bangladesh Agricultural University, 2018)
In Bangladesh, a lot of fruits and vegetables have been accused of having prolonged shelf-life by formaldehyde adulteration. So, an evaluation of the effect of formaldehyde was carried out by treating mango, litchi and oyster mushroom with different concentrations of formaldehyde and assessing their quality parameters. The three samples were dipped in 0%,1%, 5% and 10%formaldehyde solutions for 15 minutes and packed in a modified atmosphere package for observation. Changes in color, texture and weight loss were observed during storage at every alternate day. No significant increase in post-harvest quality and shelf-life was observed for mango and litchi treated with formaldehyde compared to control. Treated mushroom attained elastic texture and remained in this state up to the end of storage, whereas the control spoiled days after storage. Although formaldehyde-treated mushroom showed extended shelf-life, they lost their commercial freshness. The formaldehyde solutions did not have any significant effect on weight loss. So, formaldehyde is not a useful preservative to improve the post-harvest quality and shelf-life of fresh fruits and vegetables. J. Bangladesh Agril. Univ. 16(1): 151-157, April 2018